Role of Maternal Periodontitis in Preterm Birth - Ren, Hongyu; Du, Minquan (Frontiers in Immunology, 2017)
In the last two decades, many studies have focused on whether periodontitis is a risk factor for preterm birth (PTB). However, both epidemiological investigation and intervention trials have reached contradictory results from different studies. What explains the different findings, and how should future studies be conducted to better assess this risk factor? This article reviews recent epidemiological, animal, and in vitro studies as well as intervention trials that evaluate the link between periodontitis and PTB. Periodontitis may act as a distant reservoir of microbes and inflammatory mediators and contribute to the induction of PTB. Animal studies revealed that maternal infections with periodontal pathogens increase levels of circulating IL-1β, IL-6, IL-8, IL-17, and TNF-α and induce PTB. In vitro models showed that periodontal pathogens/byproducts induce COX-2, IL-8, IFN-γ, and TNF-α secretion and/or apoptosis in placental tissues/cells. The effectiveness of periodontal treatment to prevent PTB is influenced by the diagnostic criteria of periodontitis, microbial community composition, severity of periodontitis, treatment strategy, treatment efficiency, and the period of treatment during pregnancy. Although intervention trials reported contradictory results, oral health maintenance is an important part of preventive care that is both effective and safe throughout pregnancy and should be supported before and during pregnancy. As contradictory epidemiological and intervention studies continue to be published, two new ideas are proposed here: 1) Severe and/or generalized periodontitis promotes PTB; 2) Periodontitis only promotes PTB for pregnant women who are young or HIV-infected or have preeclampsia, pre-pregnancy obesity, or susceptible genotypes.